Mission Possible? Iraq-Syrian operation of the Bundeswehr in 2018 - Sindeev Alexey (Научно-аналитический вестник Института Европы РАН, 2018)
It is known that the Bundeswehr is a parliamentary army: its use is impossible without the consent of the Bundestag. Recently, in the print and electronic media there have been many reports about problems with the technical equipment of the Bundeswehr. At the same time, issues of content filling, changes in existing and new mandates, their comparison with each other do not attract the attention of either journalists or the public. In the Bundestag itself, the discussion of such complex matter turns into a routine and takes minimal time. By the example of one of the four mandates accepted in March 2018, the author tries to show what informative possibilities opens up a more detailed analysis. The questions posed at the end of the material can be useful for further study of the participation of the Bundeswehr in the development of NATO and the EU security structures